How effective is community quarantine in the Philippines? A quasi-experimental analysis - Marjorie C. Pajaron; Glacer Ni\~no A. Vasquez (Global Labor Organization (GLO), 2021)
As the world races to develop a COVID-19 vaccine, non-pharmaceutical interventions such as voluntary social distancing and community quarantine (CQ) have been the first line of defense in breaking the chains of transmission in most countries. The efficacy of a public health measure, however, depends on a myriad of factors including its timing and optimal implementation, the proclivity of individuals in following protocols and information dissemination. We examine whether the different types of CQ imposed at different periods and areas in the Philippines are effective in mitigating the pernicious effects of COVID-19 while controlling for other confounding factors. Our natural experiment (difference-in-differences fixed effects) using panel data that we constructed results in the following. First, a lockdown is effective only in reducing COVID-19 incidence and mortality when combined with health capacity and sociodemographic characteristics that could potentially capture preferences to comply. Second, the efficacy of a CQ persists over time but it is somewhat reduced. Third, heterogeneity in the effectiveness of a quarantine exists across the different types of CQ, with a stricter CQ apparently more effective. Fourth, the number of nurses and other health care workers, urbanity and population matter in improving the health outcomes of areas under quarantine.
Keywords: I12; I15; I18; 330; COVID-19; community quarantine; health policy intervention; quasi-experimental analysis; Philippines